The Abolition of Immigration Restrictions and the Performance of Firms and Workers: Evidence from Switzerland - Beerli, Andreas; Ruffner, Jan; Siegenthaler, Michael; Peri, Giovanni (American Economic Review, 2021)
We study a reform that granted European cross-border workers free access to the Swiss labor market and had a stronger effect on regions close to the border. The greater availability of cross-border workers increased foreign employment substantially. Although many cross-border workers were highly educated, wages of highly educated natives increased. The reason is a simultaneous increase in labor demand: the reform increased the size, productivity, and innovation performance of skill-intensive incumbent firms and attracted new firms, creating opportunities for natives to pursue managerial jobs. These effects are mainly driven by firms that reported skill shortages before the reform. (JEL J15, J23, J24, J31, J61, K37)